The mutual impedance of two circular plates for high frequency wave radiation - WITKOWSKI, P. (Archives of Acoustics, 1997)
In this paper the mutual impedance of two thin circular plates with non-axisymmetric, time-harmonic free vibrations is analyzed. It is assumed that plates clamped at the circumference are placed in a rigid, planar baffle and radiate into a lossless and homogeneous fluid medium. Damping in plates is ignored. Using the Cauchy theorem on residues and asymptotic formulae for the Bessel functions, an approximate expression is derived for a normalized mutual resistance and reactance for high frequencies.